Fluorescein angiography vs. optical coherence tomography for diagnosis of uveitic macular edema - Kempen, John H. (2013)
OBJECTIVE: To evaluate agreement between fluorescein angiography (FA) and optical coherence tomography (OCT) for diagnosis of macular edema in patients with uveitis. DESIGN: Multicenter cross-sectional study PARTICIPANTS: Four hundred seventy-nine eyes with uveitis of 255 patients METHODS: The macular status of dilated eyes with intermediate, posterior or panuveitis was assessed via Stratus-3 OCT and FA. Kappa statistics evaluated agreement between the diagnostic approaches. MAIN OUTCOME MEASURES: Macular thickening (center point thickness ≥240 μm per reading center grading of OCT images-“MT”) and macular leakage (central subfield fluorescein leakage ≥0.44 disk areas per reading center grading of FA images-“ML”); agreement amongst these outcomes in diagnosing “macular edema.” RESULTS: OCT (90.4%) more frequently returned usable information regarding macular edema than FA (77%) and biomicroscopy (76%). Agreement in diagnosis of MT and ML (κ=0.44) was moderate. ML was present in 40% of cases free of MT, whereas MT was present in 34% of cases without ML. Biomicroscopic evaluation for macular edema failed to detect 40% and 45% of cases of MT and ML respectively and diagnosed 17% and 17% of cases with macular edema which did not have MT or ML respectively; these results may underestimate biomicroscopic errors (ophthalmologists were not explicitly masked to OCT and FA results). Among eyes free of ML, phakic eyes without cataract rarely (4%) had MT. No factors were found that effectively ruled out ML when MT was absent. CONCLUSION: OCT and FA offered only moderate agreement regarding macular edema status in uveitis cases, probably because what they measure (MT and ML) are related but non-identical macular pathologies. Given its lower cost, greater safety, and greater likelihood of obtaining usable information, OCT may be the best initial test for evaluation of suspected macular edema. However, given that ML cannot be ruled out if MT is absent and vice versa, obtaining the second test after a negative result on the first seems justified when detection of ML or MT would alter management. Given that biomicroscopic evaluation for macular edema frequently erred, ancillary testing for macular edema seems indicated when knowledge of ML or MT status would affect management.